Ambulatory arterial stiffness index is associated with impaired left atrial mechanical functions in hypertensive diabetic patients: A speckle tracking study - Kalaycıoğlu, Ezgi (Anatol J Cardiol, 2015)
OBJECTIVE: The ambulatory arterial stiffness index has been proposed as an indicator of arterial stiffness. The aim of this study was to test the hypothesis that increased ambulatory arterial stiffness index might be related with impaired left atrial function in hypertensive diabetic patients with no previous history of cardiovascular disease. METHODS: Inclusion criteria included office systolic BP> 130 mm Hg or diastolic BP> 80 mm Hg and absence of secondary causes of HT, whereas exclusion criteria LV ejection fraction <50%, history of significant coronary artery disease, chronic renal failure, atrial fibrillation/flutter, second or third-degree atrioventricular block, moderate to severe valvular heart disease, history of cerebrovascular disease, non-dipper hypertensive pattern and sleep apnea. The study was composed of 121 hypertensive diabetic patients. Twenty-four-hour ambulatory blood pressure monitoring and echocardiography were performed in each patient. The relationship between ambulatory arterial stiffness index and left atrial functions was analyzed. AASI was calculated as 1 minus the regression slope of diastolic BP plotted against systolic BP obtained through individual 24-h ABPM. RESULTS: The univariate analysis showed that ambulatory arterial stiffness index was positively correlated with age (r=:0.287, p=:0.001), hypertension duration (r=:0.388, p<0.001), fasting plasma glucose (r=:0.224, p=:0.014), HbA1c (r=:0.206, p=:0.023), LDL cholesterol (r=:0.254, p=:0.005), and also overall pulse pressure (r=:0.195, p=:0.002), office-pulse pressure (r=:0.188, p=:0.039), carotid intima-media thickness (r=:0.198, p=:0.029), E/E’ (r=:0.248, p=:0.006), and left atrial volume index (r=:0.237, p=:0.009). Moreover, ambulatory arterial stiffness index was negatively correlated with eGFR (r=:(-) 0.242, p=:0.008), peak left atrial strain during ventricular systole [S-LAs (r=:(-) 0.654, p<0.001)], peak left atrial strain at early diastole [S-LAe (r=:(-)0.215, p=:0.018)], and peak left atrial strain rate during ventricular systole [SR-LAs (r=:(-) 0.607, p<0.001)]. The multiple linear regression analysis showed that ambulatory arterial stiffness index was independently associated with peak left atrial strain rate during ventricular systole (SR-LAs) (p<0.001). CONCLUSION: In hypertensive diabetic patients, increased ambulatory arterial stiffness index is associated with impaired left atrial functions, independent of left ventricular diastolic dysfunction.